Glacial landscape evolution in the Uummannaq region, West Greenland. (30th December 2015) - Lane, Timothy P.; Roberts, David H.; Ó Cofaigh, Colm; Rea, Brice R.; Vieli, Andreas
Abstract : The Uummannaq region is a mosaic of glacial landsystems, consistent with hypothesized landscape distribution resulting from variations in subglacial thermal regime. The region is dominated by selective linear erosion that has spatially and altitudinally partitioned the landscape. Low altitude areas are dominated by glacial scour and higher elevations are dominated by plateaux or mountain valley and cirque glaciers. The appearance and nature of each landscape type varies locally with altitude and latitude, as a function of bedrock geology and average glacial conditions. Selective linear erosion has been a primary control on landscape distribution throughout Uummannaq, leading to plateau formation and the growth of a coalescent fjord system in the Uummannaq region. This has allowed the development of the Uummannaq ice stream's (UIS) onset zone during glacial periods. Fjord development has been enhanced by a downstream change in geology to less‐resistant lithologies, increasing erosional efficiency and allowing a single glacial channel to develop, encouraging glacier convergence and the initiation of ice streaming. The landscape has been affected by several periods of regional uplift from 33 Ma to present, and has been subject to subsequent fluvial and glacial erosion. Uplift has removed surfaces from the impact of widespread warm‐based glaciation, leaving them as relict landsurfaces. The result of this is a regional altitude‐dependent continuum of glacial modification, with extreme differences in erosion between high and low elevation surfaces. This study indicates that processes of long‐term uplift, glacial erosion/protection and spatial variability in erosion intensity have produced a highly partitioned landscape.